The Role of Principal Leadership in Improving the Quality of Students at SDN 1 Reco, Wonosobo Regency - Astuti, Ida Dwi; Usman, Nurodin (Prosiding University Research Colloquium, 2021)
A leader plays an important role in achieving the success and goals of an organization, as well as school principals who have an important role in achieving educational and learning goals. In leading the principal must have professionalism in order to achieve educational goals, therefore the principal must play a role in the process of planning, monitoring, etc. Improving the quality of schools is one of the goals to be achieved, so to improve the quality of the institution itself, the principal must be able to foster and direct teachers to work professionally to improve the quality of students. This study aims to determine the principal’s efforts or strategies in improving the quality of students at SDN 1 Reco, Wonosobo district. The research approach used is qualitative research with data collection techniques in the form of direct interviews with related sources, namely the principal of SDN 1 Reco, Wonosobo Regency. The results showed that the principal acts as a manager, innovator, motivator by carrying out several efforts to improve the quality of students at SDN 1 Reco, Wonosobo Regency, namely trying to realize what is the school’s vision and mission, realizing active, effective and efficient learning, generating interest and student learning motivation as well as trying to improve the character and moral values of students.